Antibody cross-reactivity between casein and myelin-associated glycoprotein results in central nervous system demyelination - Chunder, Rittika; Weier, Alicia; Mäurer, Hannah; Luber, Nicolas; Enders, Michael; Luber, Gabriele; Heider, Thorsten; Spitzer, Alfred; Tacke, Sabine; Becker-Gotot, Janine; Kurts, Christian; Iyer, Radhika; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Multiple sclerosis (MS) is a neuroinflammatory demyelinating disease of the central nervous system (CNS) with a high socioeconomic relevance. The pathophysiology of MS, which is both complex and incompletely understood, is believed to be influenced by various environmental determinants, including diet. Since the 1990s, a correlation between the consumption of bovine milk products and MS prevalence has been debated. Here, we show that C57BL/6 mice immunized with bovine casein developed severe spinal cord pathology, in particular, demyelination, which was associated with the deposition of immunoglobulin G. Furthermore, we observed binding of serum from casein-immunized mice to mouse oligodendrocytes in CNS tissue sections and in culture where casein-specific antibodies induced complement-dependent pathology. We subsequently identified myelin-associated glycoprotein (MAG) as a cross-reactive antigenic target. The results obtained from the mouse model were complemented by clinical data showing that serum samples from patients with MS contained significantly higher B cell and antibody reactivity to bovine casein than those from patients with other neurologic diseases. This reactivity correlated with the B cell response to a mixture of CNS antigens and could again be attributed to MAG reactivity. While we acknowledge disease heterogeneity among individuals with MS, we believe that consumption of cow’s milk in a subset of patients with MS who have experienced a previous loss of tolerance to bovine casein may aggravate the disease. Our data suggest that patients with antibodies to bovine casein might benefit from restricting dairy products from their diet.